The evolutionary origination of a novel expression pattern through an extreme heterochronic shift. Issue 2 (24th January 2017) - Pham, Thomas; Day, Stephanie M.; Glassford, William J.; Williams, Thomas M.; Rebeiz, Mark
SUMMARY: The evolutionary origins of morphological structures are thought to often depend upon the redeployment of old genes into new developmental settings. Although many examples of cis ‐regulatory divergence have shown how pre‐existing patterns of gene expression have been altered, only a small number of case studies have traced the origins of cis ‐regulatory elements that drive new expression domains. Here, we elucidate the evolutionary history of a novel expression pattern of the yellow gene within the Zaprionus genus of fruit flies. We observed a unique pattern of yellow transcript accumulation in the wing disc during the third larval instar, a stage that precedes its typical expression pattern associated with cuticular melanization by about a week. The region of the Zaprionus wing disc that expresses yellow subsequently develops into a portion of the thorax, a tissue for which yellow expression has been reported for several fruit fly species. Tests of GFP reporter transgenes containing the Zaprionus yellow regulatory region revealed that the wing disc pattern arose by changes in the cis‐ regulatory region of yellow . Moreover, the wing disc enhancer activity of yellow depends upon a short conserved sequence with ancestral thoracic functions, suggesting that the pupal thorax regulatory sequence was genetically reprogrammed to drive expression that commences much earlier during development. These results highlight how novel domains of gene expression may arise by extreme shifts in timing during the origins of novel traits.